ACTIVATION OF INDEPENDENT STUDENT STUDY ON THE BASIS OF MODERN APPROACH - Hayitova Shakhnoza Daniyarovna (Journals Park Publishing, 2022)
This article presents the theoretical and functional structure of activating students' independent learning through the design of educational and pedagogical activities on the example of general professional sciences. Also, the pedagogical process, the pedagogical system and its stages, algorithms of educational activity, didactic materials needed to activate the independent learning of students are presented
Keywords: design; model; activation